A robust SERS calibration using a pseudo-internal intensity reference. Issue 16 (27th March 2023) - Zhang, Meng; Yang, Jingran; Yang, Longkun; Li, Zhipeng
Abstract : Reproducible SERS calibration curves were achieved using the pseudo-internal standard intensity method facilitating quantitative assays for analytes. Abstract : Surface-enhanced Raman scattering (SERS) with high molecular sensitivity and specificity is a powerful nondestructive analytical tool. Since its discovery, SERS measurements have suffered from the vulnerability of calibration curve, which makes quantification analysis a great challenge. In this work, we report a robust calibration method by introducing a referenced measurement as the intensity standard. This intensity reference not only has the advantages of the internal standard method such as reflecting the SERS substrate enhancement, but also avoids the introduction of competing adsorption between target molecules and the internal standard. Based on the normalized calibration curve, the magnitude of the R6G concentration can be well evaluated from 10 −7 M to 10 −12 M. Furthermore, we demonstrate that this pseudo-internal standard method can also work well using a different type of molecule as the reference. This SERS calibration method would be beneficial for the development of quantitative SERS analysis.